Effect of chemical treatment on physical and mechanical properties of coir fibre-polypropylene composites / Redzuan Mohammad Suffian James, Judith Gisip, Norwahyuni Mohd Yusof - James, Redzuan Mohammad Suffian; Gisip, Judith; Mohd Yusof, Norwahyuni (Universiti Teknologi MARA Shah Alam, 2023)
Research on natural fibres as reinforcement in polymer composite has increased in the past few years. Due to environmental concerns, researchers are substituting synthetic fibres with natural fibres as the main component in composites. Natural fibres have acceptable mechanical properties, material renewability, cost-effective, biodegradable and eco-friendly. This study aimed to determine the effect of chemical treatment on physical and mechanical properties of composites made from coir fibre bonded with polypropylene. Coir fibres were used as reinforcements while polypropylene was used as the matrix. Coir fibre-polypropylene composites were produced with different mixing ratios of 0:100, 10:90 and 30:70. The coir fibres were screened at 30 mesh and treated separately with alkaline and alkaline-silane. The effect of chemical treatment on water absorption, thickness swelling, bending and tensile were determined in accordance with ASTM standards (ASTM D570, ASTM D790 and ASTM D3039). Results revealed that coir fibres treated with alkaline-silane resulted in superior performance in physical and mechanical properties compared to untreated coir fibres and those that were treated with alkaline. The alkaline-silane treatment resulted in a reduced number of hydroxyl groups, thus, increasing the physical properties of the composites. Additionally, the treatment also increased the mechanical properties by improving the level of adhesion between the fibre and matrix. In conclusion, chemical treatment improves the strength and properties of coir fibre-polypropylene composites and can be used as a potential product for various industries.